2017
DOI: 10.1007/s00330-017-5026-2
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic resonance imaging for clinical management of rectal cancer: Updated recommendations from the 2016 European Society of Gastrointestinal and Abdominal Radiology (ESGAR) consensus meeting

Abstract: ObjectivesTo update the 2012 ESGAR consensus guidelines on the acquisition, interpretation and reporting of magnetic resonance imaging (MRI) for clinical staging and restaging of rectal cancer.MethodsFourteen abdominal imaging experts from the European Society of Gastrointestinal and Abdominal Radiology (ESGAR) participated in a consensus meeting, organised according to an adaptation of the RAND-UCLA Appropriateness Method. Two independent (non-voting) Chairs facilitated the meeting. 246 items were scored (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
532
0
15

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(562 citation statements)
references
References 36 publications
15
532
0
15
Order By: Relevance
“…The previous study confirmed that in colorectal patients with only one metastatic LN, the 5‐year survival rate was significantly higher than those with greater than or equal to two LNs (67% to 39.6%) . Some MRI studies also established that the number of MR‐LN should be included in the assessment of rectal cancer . Our study found that the MR‐LN numbers were different in subgroups, and that was considered as the risk factor of LNM in univariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The previous study confirmed that in colorectal patients with only one metastatic LN, the 5‐year survival rate was significantly higher than those with greater than or equal to two LNs (67% to 39.6%) . Some MRI studies also established that the number of MR‐LN should be included in the assessment of rectal cancer . Our study found that the MR‐LN numbers were different in subgroups, and that was considered as the risk factor of LNM in univariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 85%
“…Pathologically, LVI or vascular infiltration was suggested as a significant risk factor for LNM or distant metastasis in other surveys . At the European Society of Gastrointestinal and Abdominal Radiology Consensus Conference, the shape, border, and signal heterogeneity of LNs were considered as morphologically suspicious criteria, and our research had a similar result with that …”
Section: Discussionsupporting
confidence: 76%
“…Nodes with an irregular margin or heterogeneous internal signal were judged as suspicious of metastasis, and those smaller than 5 mm were generally considered benign. These are similar to expert recommendations. The readers tended to apply a sensitive threshold when interpreting equivocal subjective nodal findings to help avoid neglecting subtle metastatic nodes, given that most patients were to undergo CRT regardless, according to the NCCN guidelines.…”
Section: Methodsmentioning
confidence: 64%
“…ADC is the worst performing model, with an AUC value of 0.60, whereas IVIM‐Kurtosis is the best performing model with an AUC of 0.73; however, the difference does not reach statistical significance according to the DeLong test ( P = .19) . Figure C shows that IVIM‐Kurtosis also provides a better differentiation between benign and malignant nodes (AUC = 0.80) compared to the standard clinical T 2 classification based on the European Society of Gastrointestinal and Abdominal Radiology 2016 criteria (AUC = 0.74 for reader 1; AUC = 0.59 for reader 2), which takes into consideration lymph node size, shape, contour, and heterogeneity. Moreover, combining IVIM‐Kurtosis and T 2 results significantly improves the classification compared to T 2 ‐weighted images alone ( P = .08 for reader 1; P = 0.007 for reader 2).…”
Section: Resultsmentioning
confidence: 95%